Is India ripe for integrated water resources management?: fitting water policy to national development context - Shah, Tushaar; van Koppen, Barbara (2006)
Water scarcity has emerged, especially during the past decade, as an important theme in discussions on India's future. Global discourse suggests that India, and other developing countries in Asia and Africa, can respond to water scarcity - and the resultant water poverty facing their people - by embracing integrated water resources management, a package of best practices for improved management of water resources with strong emphasis on direct demand-side management. This paper addresses five questions about the IWRM paradigm with respect to India: (1) Is water poverty of countries caused by their water scarcity?(2) Would embracing IWRM help alleviate India's water poverty? (3) Is implementing IWRM feasible in India in today's context? (4) Has implementing IWRM helped counter water scarcity and poverty in other countries with a development context comparable to India's? And, finally, (5) What should be the priorities and roadmap for improving the working of the water sector in India? The paper reviews recent evidence from around the world to analyse these questions and concludes with a discussion of implications for water sector reform discussions in India.